World History Cultures, States, and Societies to 1500 - Berger, Eugene; Israel, George L.; Miller, Charolette (Open textbook library., 2016)
World History: Cultures, States, and Societies to 1500 offers a comprehensive introduction to the history of humankind from prehistory to 1500. Authored by six USG faculty members with advance degrees in History, this textbook offers up-to-date original scholarship. It covers such cultures, states, and societies as Ancient Mesopotamia, Ancient Israel, Dynastic Egypt, India's Classical Age, the Dynasties of China, Archaic Greece, the Roman Empire, Islam, Medieval Africa, the Americas, and the Khanates of Central Asia.It includes 350 high-quality images and maps, chronologies, and learning questions to help guide student learning. Its digital nature allows students to follow links to applicable sources and videos, expanding their educational experience beyond the textbook. It provides a new and free alternative to traditional textbooks, making World History an invaluable resource in our modern age of technology and advancement.